2015
DOI: 10.1093/cvr/cvv280
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2c increases in atrial myocytes from chronic atrial fibrillation patients enhancingIKsand decreasingICa,L

Abstract: Our results demonstrated for the first time that CAF increases Pitx2c expression in isolated human atrial myocytes and suggested that this transcription factor could contribute to the CAF-induced IKs increase and ICa,L reduction observed in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
91
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 34 publications
10
91
0
2
Order By: Relevance
“…Therefore, Tbx20 effects on the L-type Ca 2+ current (I CaL ) were tested in both HL-1 cells and hiPSC-CMs. In HL-1 cells, I CaL was measured using Ba 2+ as a charge carrier (I Ba ) (15,18). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, Tbx20 effects on the L-type Ca 2+ current (I CaL ) were tested in both HL-1 cells and hiPSC-CMs. In HL-1 cells, I CaL was measured using Ba 2+ as a charge carrier (I Ba ) (15,18). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HL-1 and Chinese hamster ovary cells were transiently transfected by using Lipofectamine 2000 and FuGENE X-tremeGENE, respectively, and cultured as described (15,17,18,30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 We have found that symptomatic response to antiarrhythmic drug therapy is at least partially modulated by common single-nucleotide polymorphisms at the chromosome 4q25 locus. 5 Pérez-Hernández et al 6 showed that patients with chronic AF have a significantly higher expression of Pitx2c messenger RNA vs normal sinus rhythm controls; enhanced Pitx2c expression in HL-1 atrial myocytes results in an increase in slow delayed rectifier potassium current (I Ks ) and decrease in L-type calcium current (I Ca,L ), which are hallmarks of AF. More recently, the AFGen Consortium has identified 12 new genetic loci associated with AF.…”
mentioning
confidence: 99%